The Effect Of The Work Environment On Employee Performance With Job Satisfaction As A Moderating Variable In The Binjai City Social Service - Hendra Fereddy Sitorus; Mesra B (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the influence of the work environment on employee performance with job satisfaction as a moderation variable at the Binjai City Social Service. This study uses a casual associative quantitative method with data analysis techniques using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). Data was collected through a questionnaire distributed to 55 employees within the Binjai City Social Service. The results of the study show that the work environment has a positive and significant influence on employee performance with a T-Statistic value of 2.590 (> 1.96) and a P-Value of 0.012 (< 0.05). On the other satisfaction did not have a significant influence on employee performance, with a T-Statistic value of 1.470 (< 1.96) and a P-Value of 0.147 (> 0.05). In addition, job satisfaction also did not moderate the relationship between the work environment and employee performance, with a T-Statistic value of 0.791 (< 1.96) and a P-Value of 0.219 (> 0.05). These findings confirm that a conducive work environment is an important factor that affects employee performance. However, job satisfaction does not contribute significantly either directly or as a moderation variable. This study recommends improving the quality of the work environment through adequate facilities, good working relationships, and management support to improve employee performance.